YAP1 plays a key role of the conversion of normal fibroblasts into cancer-associated fibroblasts that contribute to prostate cancer progression - Tianyu Shen; Yang Li; Shimiao Zhu; Jianpeng Yu; Boya Zhang; Xuanrong Chen; Zheng Zhang; Yuan Ma; Yuanjie Niu; Zhiqun Shang (Journal of Experimental & Clinical Cancer Research, 2020)
Abstract Background Cancer-associated fibroblasts (CAFs) are an important part of the tumour microenvironment, and their functions are of great concern. This series of experiments aimed to explore how Yes-associated protein 1 (YAP1) regulates the function of stromal cells and how the normal fibroblasts (NFs) convert into CAFs in prostate cancer (PCa). Methods The effects of conditioned media from different fibroblasts on the proliferation and invasion of epithelial cells TrampC1 were examined. We then analysed the interaction between the YAP1/TEAD1 protein complex and SRC, as well as the regulatory function of the downstream cytoskeletal proteins and actins. A transplanted tumour model was used to explore the function of YAP1 in regulating tumour growth through stromal cells. The relationship between the expression of YAP1 in tumour stromal cells and the clinical characteristics of PCa patients was analysed. Results The expression level of YAP1 was significantly upregulated in PCa stromal cells. After the expression level of YAP1 was increased, NF was transformed into CAF, enhancing the proliferation and invasion ability of epithelial cells. The YAP1/TEAD1 protein complex had the capability to influence downstream cytoskeletal proteins by regulating SRC transcription; therefore, it converts NF to CAF, and CAF can significantly promote tumour growth and metastasis. The high expression of YAP1 in the tumour stromal cells suggested a poor tumour stage and prognosis in PCa patients. Conclusion YAP1 can convert NFs into CAFs in the tumour microenvironment of PCa, thus promoting the development and metastasis of PCa. Silencing YAP1 in tumour stromal cells can effectively inhibit tumour growth.